Psychosocial Determinants of Marijuana Utilization among Selected Junior High School Students in the Central Region of Ghana - Thomas Hormenu; Hagan Jnr. John Elvis; Schack Thomas; Pollmann Dietmar (Journal of Preventive Medicine And Care, 2018)
Marijuana utilization among school aged adolescents is major public and mental health concern in Ghana and other developing countries, with the rate of usage soaring high among school going adolescents. The objective of this study was to investigate the prevalence of marijuana utilization among selected Junior High School (JHS) students in the Central Region of Ghana and explore the relative impact of psychosocial factors accounting for its usage. Using a descriptive cross-sectional survey design with the Global School Based Survey GSHS questionnaire, a sample of 1400 school going adolescents students were drawn using multistage sampling procedure. Frequencies, percentages and binary logistic regression results indicated marijuana utilization prevalence of 9% (n = 122). Statistically, gender (OR = 0.52, 95% CI= 0.35 - .765, p = 0.001), religious affiliation (OR = 1.76, 95% CI = 1.0 - 2.95, p = 0.034), socioeconomic background (OR = 0.52, 95% CI = 0.33 - 1.23, p = 0.004) and geographical location (OR = 0.53, 95% CI = 0.31 - .886, p = 0.016) significantly predicted marijuana utilization among school aged adolescents. No statistically significant variations were found in the odds of students’ marijuana usage for age (OR = 1.15, 95% CI = 0.69 - 1.88, p = 0.590), parental communication (OR = 0.83, 95% CI = 0.56 - 1.23, p = 0.348) and academic performance (OR = 1.09, 95% CI = 0.66 -1.80, p = 0.744). Findings suggest that school based research should reﬂect and perhaps replicate existing prevalence, patterns of marijuana and other drug use through multiple school surveys nationwide. This pathway may provide useful information towards the design, evaluation and implementation of drug prevention cognitive-behavioural interventions and the development of stringent drug regulative standards.
Keywords: ‘‘Wee’’ usage